Strengthening Character Education Preparing the Golden Generation with 21st Century Skills - Yusuf, Arba'iyah; Tajab, Muh. (Postgraduate Program Magister Pendidikan Agama Islam, 2023)
This research is motivated by the fact that character education is the core of education throughout the world. In 2016, the Indonesian government's policy on strengthening character education was established. The hope is that in 2045 a golden generation will be born, so that it needs to be equipped with 21st century skills. The research method used to uncover this problem is through a qualitative approach, because qualitative research aims to understand the meaning or explore certain phenomena, events, facts, realities, or problems related to social and human aspects in depth. The type of research used in this study is a literature study. The results of the study show that there are three policies related to strengthening character education, namely Presidential Regulation number 87 concerning strengthening character education in 2017, Minister of Education and Culture Regulation number 20 regarding strengthening character education in 2018 and the profile of Pancasila students in 2020. Second, the bright next generation in 2045 needs to be prepared with 21st century skills. The response to world changes and the post-pandemic era begins with changes in character education as the main goal in preparing for the golden generation. The transformation of national education in Indonesia aims to provide responses and solutions to new challenges, demands and needs that arise as a result of various current situations. This confirms that the arrangement or transformation of Indonesia's national education is a very important historical task and must be carried out in earnest.